Systematization of nursing care and implementation of the multidisciplinary team in the preoperative period of cardiac surgery: integrative literature review (Research, Society and Development, 2022)
Objective: to carry out an integrative review of the literature that presents results in scientific databases on the systematization of nursing care and the implementation of the multidisciplinary team; synthesize the synthesis of the information obtained in the literature on the systematization of nursing care during cardiac surgical preoperative; list the importance of such knowledge for the improvement of knowledge and the process of care. Methodology: This is an exploratory and descriptive study, with a qualitative approach of the integrative review type of literature. With the use of IRaMuTeQ to list the discursive classes resulting from the analyses of the selected articles. The database chosen was the VHL. Results and discussion: 11 articles were selected from the database search, in relation to the discursive class erated by IRaMuTeQ, the result was 1) Alternative techniques such as intervention to prevent depression and anxiety preoperatively; 2) Guidance on doubts regarding cardiac surgery in the preoperative period; 3) Health education in the promotion of self-care in the cardiac operative foot; 4) Importance of multiprofessional care in cardiac preoperative; 5) More frequent preoperative cardiac symptoms. Conclusion: It is concluded that cardiovascular diseases are considered the main causes of mortality in the world and a higher percentage of deaths worldwide, which represents a major public health problem. Among the treatment alternatives are cardiac surgeries in their various modalities. However, because it is a high-risk procedure, it results in fear and anxiety for patients.